1974
DOI: 10.2307/1934418
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Selection of Breeding Birds in an East Tennessee Deciduous Forest

Abstract: Bird populations were sampled between May 30 and July 20, 1972, on twenty—four 0.08—ha plots on Walker Branch Watershed, a primarily deciduous forest located in Anderson County, Tennessee. Univariate analysis of variance was used to test for differences in abundance categories of each bird species with respect to 28 habitat variables. Differences in habitat preferences within major bird families (Picidae, Parulidae, Paridae, and Thraupidae) were apparent from this analysis. Discriminant function analysis was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(87 citation statements)
references
References 16 publications
6
78
0
1
Order By: Relevance
“…These results were consistent with the widely held view that vegetation structure and habitat configuration ("physiognomy";Whittaker 1975) are more important to the determination of habitat occupancy patterns of birds than the particular plant taxonomic composition (" floristics") of the vegetation (e.g., Hild6n 1965;Wiens 1969;James 1971;Anderson and Shugart 1974). Indeed, a variety of studies have shown strong associations between physiognomy and patterns of species distributions and community structure (e.g., MacArthur and MacArthur 1961;MacArthur et al t966;Willson 1974;James and Wamer 1982).…”
supporting
confidence: 87%
“…These results were consistent with the widely held view that vegetation structure and habitat configuration ("physiognomy";Whittaker 1975) are more important to the determination of habitat occupancy patterns of birds than the particular plant taxonomic composition (" floristics") of the vegetation (e.g., Hild6n 1965;Wiens 1969;James 1971;Anderson and Shugart 1974). Indeed, a variety of studies have shown strong associations between physiognomy and patterns of species distributions and community structure (e.g., MacArthur and MacArthur 1961;MacArthur et al t966;Willson 1974;James and Wamer 1982).…”
supporting
confidence: 87%
“…A number of quantitative and observable 3D forest structure characteristics are 273 needed to characterize habitat (canopy cover, tree and canopy height, vertical structure, 274 and tree volume) [MacArthur and MacArthur, 1961;Anderson and Shugart 1974; 275 Willson 1974;Morgan and Freedman 1986]. As described in section 1.3 these same 276 variables are also needed to estimate biomass.…”
Section: Information Needs For Habitat and Biodiversity 272mentioning
confidence: 99%
“…The total amount of carbon contained in the forest's biomass is not known to even 232 one significant Figure. Estimates range from 385 to 650 PgC (Saugier et al 2001, FAO 233 2001, Goodale et al 2002 and tree volume) [MacArthur and MacArthur, 1961;Anderson and Shugart 1974;275 Willson 1974;Morgan and Freedman 1986]. As described in section 1.3 these same 276 variables are also needed to estimate biomass.…”
Section: Information Needs For the Global Carbon Budget 231mentioning
confidence: 99%
“…Habitat structure and floristic composition may be used to discriminate among habitats and possible nest sites (Anderson & Shugart 1974;Bergin 1992;Bence et al 1999;Wagner et al 2000;Kershner et al 2001). …”
Section: Introductionmentioning
confidence: 99%